Penerapan Media Pop-Up Book untuk Meningkatkan Minat Belajar Siswa pada Pembelajaran IPAS MI Malik Ibrahim - Tri Hany Nur Safitri; Muhammad Suwignyo Prayogo; Nurmala Karima; Nabila Sevidiana (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
This study aims to apply pop-up book media to human senses in IPAS learning to improve the learning interest of fourth grade students of MI Malik Ibrahim Jenggawah. The background of this study shows the low interest in learning of students which has a negative impact on their academic achievement. Students who are not interested in reading and rarely do so tend to have difficulty in understanding the subject matter. This study uses the Classroom Action Research (CAR) method which consists of four stages, namely planning, action, observation, and reflection. Data collection includes observation, and documentation. Data analysis techniques use descriptive qualitative approach analysis. The results of the study showed that there was a significant increase in students' learning interest after the application of pop-up book media. After the action was carried out, students were more enthusiastic, participated and understood. The study shows that the use of pop-up book media can create a pleasant and effective atmosphere in learning.